The Role of the Regional Technical Implementation Unit (UPTD) Griya Wanita Mandiri in Supporting the Social Rehabilitation of Prostituted Women - Siti Nuraeniyah Jamalilail; Kiki Endah; Regi Refian Garis (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This research aims to evaluate the role of the Regional Technical Implementation Unit (UPTD) of the Griya Wanita Mandiri Social Service Centre in supporting social rehabilitation programmes for homeless women, as well as explore their future orientation in meeting the developmental and rehabilitation needs of women who are homeless. Conducted from October 2023 to June 2024, this research used qualitative methods such as interviews and observations. The results showed that the role and skills of the social service centre in facilitating the utilisation of the skills and resources of prostituted women have been running effectively. However, the motivation provided by social workers to prostitute women is still not optimal. In the role and skills of education, social workers have been able to provide physical, health, and recreational guidance training to prostituted women. Spiritual awareness provided through spiritual guidance still needs to be improved. The role and skills of representation have gone well, as evidenced by the programmes organised by the social service centre that have provided adequate understanding to prostituted women through social rehabilitation services. However, the social problem-solving by the social service centre for women who are prostitutes is not yet optimal, as evidenced by the ineffective relationship between social workers and fellow caseworkers in carrying out social rehabilitation for women who are prostitutes.